For the carpet:
Given:
Area = x^2 + x - 20 ft^2
Length = x+ 5 ft
As a carpet is rectangular, the area is defined as the product of the length and the width. To obtain an expression of the carpet's width, the area is to be divided by the length, which is shown below:
__x_-_4___x + 5|x^2 + x - 20 x^2 + 5x -------- -4x - 20 -4x - 20 -------- 0
Therefore, the expression of width = x - 4.
Applying the value of x = 20 to obtain the measurements of the carpet, we obtain the following:
Width = x - 4 = 20 - 4 = 16ft
Length = x+ 5 = 20 + 5 = 25ft.
Therefore, the carpet is 25ft x 16ft.
For the wall:
The same principles apply to the wall as it is also assumed to be rectangular.
Given:
Area = <span>x^2 + 17x + 30 ft^2
Width = x + 2
To obtain the expression for the wall's length, Area is to be divided by the Width, which is shown below:
__x_+_15______x + 2|x^2 + 17x + 30 x^2 + 2x -------- 15x + 30 15x + 30 --------- 0
Therefore, the expression for the wall's length is x + 15.
Applying the value of x = 20 to obtain the wall's dimensions:
Length = x + 15 = 20 + 15 = 35ft.
Width = x + 2 = 20 + 2 = 22ft.
Therefore the wall has measurements of 35ft x 22ft.</span>
FOR THE FIRST PROBLEM:
Differentiating p^2 + 2q^2 = 1100 with respect to time => 2p(dp/dt) + 4q(dq/dt) = 0
<span>dp/dt = -2q/p(dq/dt) </span>
<span>R = pq </span>
<span>dR/dt = p(dq/dt) + q(dp/dt) = -p²/2q(dp/dt) + q(dp/dt) = (2q² - 1100)/2q * (dp/dt) + q(dp/dt) </span>
<span>A = (2q - 550/q)
I hope my answer has come to your help. Thank you for posting your question here in Brainly. We hope to answer more of your questions and inquiries soon. Have a nice day ahead!
</span>
Answer:
6) 22,408
7) 8,993
8) 68,701
Step-by-step explanation:
6) 122408 - 100000 = 22,408
7) 8993/999 = 9 2/999
8) 98,700 - 29,999 = 68,701
The next step is to solve the recurrence, but let's back up a bit. You should have found that the ODE in terms of the power series expansion for
which indeed gives the recurrence you found,
but in order to get anywhere with this, you need at least three initial conditions. The constant term tells you that
, and substituting this into the recurrence, you find that
for all
.
Next, the linear term tells you that
, or
.
Now, if
is the first term in the sequence, then by the recurrence you have
and so on, such that
for all
.
Finally, the quadratic term gives
, or
. Then by the recurrence,
and so on, such that
for all
.
Now, the solution was proposed to be
so the general solution would be
Answer:
x is less then or equal to -3
x<-3 (the < has to have a line underneath)
Step-by-step explanation: